Plasma pharmacokinetics of once-daily abacavir- and lamivudine-containing regimens and week 96 efficacy in HIV-infected Thai children - Torsak Bunupuradah; Passorn Punyahotra; Tim R. Cressey; Amornrat Srimuan; Narukjaporn Thammajaruk; Jiratchaya Sophonphan; Chulalak Sriheara; David M. Burger; Thanyawee Puthanakit; Jintanat Ananworanich (Journal of Virus Eradication, 2015)
Background: Abacavir and lamivudine are approved for once-daily use in HIV-infected adults Limited pharmacokinetic (PK) data for abacavir and lamivudine in children are available. Methods: A crossover study to compare PK of once- versus twice-daily abacavir and lamivudine was conducted in virologically suppressed HIV-infected Thai children aged <18years, with bodyweight of at least 14 kg, HIV RNA <50 copies/mL and HLA-B*5701 negative. Abacavir and lamivudine daily doses by bodyweight were 300 and 150 mg for 14–<20 kg, 450 and 300 mg for 20–<25 kg, and 600 and 300 mg for ≥25 kg, respectively. Originator abacavir and lamivudine scored tablets were administered. Intensive PK sampling was performed after 14 days of each dose. PK parameters were determined using non-compartmental analysis. Results: Thirty children (57% male) were enrolled, 10 per weight band. Median (IQR) age was 8.8 (6.6–11.3) years and bodyweight was 21.9 (19.2–30.6) kg. The geometric means (GM) AUC0–24 of once- and twice-daily abacavir were 14.43 and 10.65 mg.h/L, respectively. The geometric mean ratio (GMR) of AUC0–24 for once- versus twice-daily abacavir dosing was 1.36 [90% confidence interval (CI) 1.11–1.66]. The GM AUC0–24 of once- and twice-daily lamivudine were 17.70 and 18.11 mg.h/L, respectively. The GMR of AUC0–24 for once- versus twice-daily lamivudine dosing was 0.98 (90% CI 0.84–1.14). At 96 weeks, 90% had HIV RNA <50 copies/mL and there were no serious adverse events. Conclusion: Abacavir exposure was greater with once-daily dosing, while lamivudine once- and twice-daily exposures were bioequivalent. Once-daily abacavir and lamivudine using weight-band dosing is a treatment option for children.